PENGARUH FINANCIAL DISTRESS DAN AUDIT CLIENT TENURE TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI tahun 2010-2012) - Dhama Lisan Shidqi; Sutapa Sutapa (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2014)
This research aimed to show empirical proves about the effect of financial distress and audit client tenure to an acceptance of going concern audit opinion. Hypothesis proposed by the researcher were (1) Financial distressnegatively affected to the acceptance of going concern audit opinion, (2) Audit client tenure negatively affected to the acceptance of going concern audit opinion. The sample of this research was manufacturing firm in the period of 2010-2012. Purposive sampling technique was used to obtain the sample. Logistic regression was used to analyze the data. The variables of this research were financial distress and audit client tenure. The result shows that financial distress have negatively affected on the acceptance of going concern audit opinion, while audit client tenure do not have significant effect on the acceptance of going concern audit opinion.